Philosophy Perspective of Mathematics Education as a Field of Knowledge - Telaumbanua, Yakin Niat; Dewi, Izwita; Simamora, Elmanani (STAI Miftahul Ula Nganjuk, 2023)
Philosophy of education is essentially the application of philosophical ways of thinking into the realm of education. Philosophy helps the process of implementing mathematics education. Philosophy directs and guides all processes that take place in mathematics education, so that education is carried out according to the right path and direction. The purpose of this study is to examine in depth how the philosophy of mathematics education perspective as a field of knowledge. The research method in this study used the literature study method. Data collection was carried out by collecting data from the library, from research journals and books and then reading, recording and processing these sources as research data. Philosophy of mathematics education as a field of knowledge provides a clear basis and direction for mathematics to become a means of thinking in discovering and developing various new knowledge and will then communicate the results of this knowledge so that it becomes useful and usable. Based on the study of ontology and epistemology, in carrying out mathematics education activities as a field of knowledge it is necessary to apply a philosophy of mathematics which involves the use of logic and the involvement of students in constructing their knowledge in solving existing phenomena or problems. Based on the axiological study, mathematics education as a field of knowledge will have value if students in the implementation of mathematics education are organized by involving the connections of mathematics with other sciences and connections with previously acquired knowledge.